Potrzeby informacyjne controllingu w obszarze sprzedaży przedsiębiorstwa handlowego - Lew, Grzegorz (Informative Needs of Controlling in the Area of Sales of an Enterprise., 2006)
The paper presents informative needs of controlling in the area of sales, especially enterprises. The informative needs of controlling concern mainly all information necessary to create the sales budget and others connected with this budget.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 34-42